Local wisdom on Java manuscript in Banyuwangi: study of Indonesia culture’s value - ROFIQ, A. A; ANSHORI, S.; UMARELLA, S.; SAMBADA, D.; INDRIANI, D. E (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT An attempt to study Indonesian culture in the Java region is being made to explore the values of wisdom found in one of Banyuwangi’s most influential manuscripts. This study reveals richness culture value written on Lontar Yusuf as java manuscript, which mostly influenced by the Islamization process using content analysis. The aim of this cultural research on selected java manuscript is to study literary works that are part of indigenous Indonesian culture; explore the culture of Banyuwangi, mainly to search the local wisdom behind this cultural heritage that could be used for the counseling purpose. RESUMEN Se está intentando estudiar la cultura indonesia en la región de Java para explorar los valores de la sabiduría que se encuentran en uno de los manuscritos más influyentes de Banyuwangi. Este estudio revela el valor de la cultura de riqueza escrito en Lontar Yusuf como manuscrito de Java, que fue influenciado principalmente por el proceso de islamización mediante el análisis de contenido. El objetivo de esta investigación cultural sobre el manuscrito seleccionado de Java es estudiar obras literarias que son parte de la cultura indígena indonesia; explora la cultura de Banyuwangi, principalmente para buscar la sabiduría local detrás de este patrimonio cultural que podría usarse para el propósito de asesoramiento.